Boundary exchange completes the marine Pb cycle jigsaw - Chen, Mengli (2023)
Material fluxes at the land-ocean interface impact seawater composition and global cycling of elements. However, most attention has been focused on the fluvial dissolved fluxes. For elements like lead (Pb), whose fluvial particulate flux into the ocean is two orders of magnitude higher than the dissolved counterpart, the role of particulates in elemental cycling is potentially important but currently less appreciated. Using both chemical analyses on samples collected from around equatorial Southeast Asia and model simulations, we show that particulate-dissolved exchange is an important mechanism controlling the concentration and isotopic composition of dissolved Pb in the ocean. Our model indicates that Pb contributed from particulate-dissolved exchange at ocean boundaries is larger than, or at least comparable to, other major Pb sources to the seawater before the Anthropocene, when the anthropogenic Pb was absent. Our work highlights the importance of boundary exchange in understanding marine element cycling and weathering-climate feedback.